Supramolecular Chromatographic Separation of C 60 and C 70 Fullerenes: Flash Column Chromatography vs. High Pressure Liquid Chromatography - Mekapothula, Subbareddy; Wonanke, A D Dinga; Addicoat, Matthew A; Boocock, David J; Wallis, John D; Cave, Gareth W V (International journal of molecular sciences, 2021)
A silica-bound -butylpyrogallol[4]arene chromatographic stationary phase was prepared and characterised by thermogravimetric analysis, scanning electron microscopy, NMR and mass spectrometry. The chromatographic performance was investigated by using C and C fullerenes in reverse phase mode via flash column and high-pressure liquid chromatography (HPLC). The resulting new stationary phase was observed to demonstrate size-selective molecular recognition as postulated from our in-silico studies. The silica-bound -butylpyrogallol[4]arene flash and HPLC stationary phases were able to separate a C - and C -fullerene mixture more effectively than an RP-C stationary phase. The presence of toluene in the mobile phase plays a significant role in achieving symmetrical peaks in flash column chromatography.